PECULIARITIES OF EXPORT-IMPORT OPERATIONS OF AGRICULTURAL PRODUCTS UNDER MARTIAL LAW - MURAVSKA, Lesya; RUDA, Tatyana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to study the peculiarities of export-import operations of agricultural products under martial law. The war radically changed the conditions of conducting business, in particular, it affected foreign economic activity. The article examines the peculiarities of export-import operations in the conditions of blockade of sea ports, disruption of stable logistics chains and significant increase in logistics costs. The legislative changes affecting the procedure for carrying out export-import operations with the participation of domestic business entities were analyzed. The article also analyzes the main trends in foreign trade in agricultural products, in particular, grain crops. The issue of the "grain agreement" and its features have been studied. It was established that the regulation of foreign economic activity has positive results. According to the results of the first half of the year, agricultural products maintained a dominant position in the volume of exports from Ukraine, despite the five-month blockade of the main sales channel - ports on the Black Sea. Therefore, the study of export-import operations of agricultural products is an urgent problem. Currently, companies that are just starting to enter foreign markets have a whole arsenal of support tools — from foreign market analytics, educational events and consulting, foreign partner search tools to grants from the state and donor organizations. Prospects for the development of exports in the conditions of war are determined, given the limited economic and organizational capabilities. The conducted analysis of the dynamics of foreign trade of Ukraine, the structure of export of agricultural products, logistical features of trade indicates the need to develop new approaches to the organization of foreign trade under martial law conditions.